DIGITAL ASSESSMENT INFUSED WITH CULTURALLY RESPONSIVE TEACHING: EFL LEARNER PERCEPTIONS ON TECHNOLOGICAL INCLUSIVENESS - Slamet Asari (Indonesian EFL Journal, 2025)
Culturally Responsive Teaching (CRT) is a learning approach that emphasizes the value of respecting and incorporating students' cultures into the learning process. Along with this approach, there is a desire for more culturally sensitive assessments that take into account the students' background characteristics or cultures. The purpose of this study is to acquire an overview of EFL learners' impressions of the CRT approach, which incorporates digital assessment into learning. This study used a mixed-method design to gather and process data from 124 secondary-level students, employing questionnaires and observations for the instruments. It was then analyzed using descriptive statistics and qualitative analysis. It was discovered that EFL learners had positive attitudes toward the use of CRT-based digital assessments, notably in terms of comfort, convenience, and relevance to their culture they have experienced. Their motivation and involvement in learning supported this finding, leading to significant and beneficial outcomes. They felt more respected, intrigued, and connected to ordinary situations, and their confidence was leveraged. However, the challenges and obstacles encountered necessitate careful consideration, in particular the time provided for completing the assessment and the inadequacy of some test elements to accommodate a small group of students.